Land of the Trinity - Godfrey (Journal of Dharma, 1977)
The Church today is aware that she is called to be a partner in dialogue with other religions "to achieve a deeper understand- ing of the Gospel's newness and of the fullness of revelation". The Church in India, too, following the pattern of the universal Church, is entering a new era of dialogue. The possibilities are being explored for a meeting of religions in areas of religious scriptures, philosophy, theology, spirituality and so on. And the book "Land of Trinity", is a rich and remarkable contribution to this line of approach.